Perawatan luka pada anjing penderita demodekosis di Klinik Hewan Bogor Pet Center Bogor - Henny Endah Anggraeni; Wily Widya Komara; Feni Dwi Kartika Gulo; Mustika Hidayanti (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
Demodecosis is a skin disease caused by mites Demodex sp. The mites can cause itching and made scratching reflex and made skin damage or wound. Wound is a damage conditions in the skin tissues. Wound care for demodecosis of Pitbull mix dog at Bogor Pet Centre Clinic began with treatment the myiasis and clean the wound 2 times a day and the treatment continues until 19 days topically and orally. Wound healing works well